Oral health inequalities in a national sample of Australian children aged 2–3 and 6–7 years - Nicholson, J.M; Nicholson, J; Chapman, J; Lucas, N; Kilpatrick, N; Kilpatrick, N.M; Neumann, A (My University, 2012)
Background: While inequalities in oral health are generally well documented, it is less clear whether such patterns are evident from early childhood. Using four measures of potential inequality, this study examined patterns in oral health for Australian children at ages 2–3 and 6–7 years. Methods: Cross-sectional data from two cohorts of children in the Longitudinal Study of Australian Children (LSAC) were used to explore associations between reported oral health and four indicators of social disadvantage: socio-economic position (SEP), residential remoteness, Indigenous status and non-English speaking background. Results: For both cohorts, lower SEP and Indigenous status were associated with higher odds of poor oral health on all three indicators, and less accessible location was associated with increased odds for caries. Non-English speaking background was associated with increased odds for caries experience in 2–3 year olds and non-use of dental services in the older cohort. Inequalities were larger in the older cohort for socio-economic position and toothbrushing. Conclusions: Marked social disparities in oral health appear as early as 2 years of age and remain evident in school-age children. Interventions to reduce such disparities should start as early as possible.
Keywords: Children; Location -- Rural and remote; Health -- Dental; Children -- Indigenous; Housing, communities and neighbourhoods; Health and wellbeing; Location; Health; Children; Rural and remote; Dental; Indigenous; Housing, communities and neighbourhoods; Health and wellbeing